Measurements and Accuracy of IgM and IgG Anti Phenolic Glycolipid-1 Levels in Blood Serum for Early Detection Mycobacterium leprae by using Enzyme-Linked Immunosorbent Assay (ELISA): A Reality of a Laboratory - Abdullah, Salsabilla Putri Kinanti; Dinar Adriaty; Iswahyudi; Puput Ade Wahyuningtyas; Laura Navika Yamani; Medhi Denisa Alinda; Ratna Wahyuni; Cita Rosita Sigit Prakoeswa (Institute of Topical Disease Universitas Airlangga, 2023)
Indonesia was the third most recent case of leprosy globally in 2020 with 11,173 people, after India and Brazil. Most of the leprosy manifestations are asymptomatic. This is possibly as subclinical leprosy which individuals without leprosy symptoms but have leprosy specific antibodies high levels, so it has the potential to become a transmission and disability. Therefore, an ELISA test need for early detection in preventing leprosy transmission. This study aims to measure IgM and IgG antibody levels in leprosy patients and assess the accuracy of the measurement results. This research is a cross-sectional study. Five patients' blood samples have analyzed for IgM and IgG anti-PGL-1 antibody levels by ELISA. Accuracy interpretation of this measurement based on the %CV. Antibody levels were classified based on the cut-off <605 u/ml as IgM seronegative or <630 u/ml as IgG seronegative, 605–1000 u/ml as low seropositive IgM or 630-1000 u/ml as low seropositive IgG, and >1000 u/ml as high seropositive IgM and IgG. Among five patients examined, 40% had high seropositive leprosy with anti-PGL-1 IgM and IgG antibody titers>1000 u/ml, and 60% of patients had seronegative leprosy. Accuracy in this ELISA test shows high accuracy with %CV <10% in the conversion of OD to antibody titer levels. IgM and IgG Anti PGL-1 antibody titers by ELISA as one of the parameters in identifying patients at higher risk of leprosy. A significant portion of patients with high seropositive leprosy with high accuracy.